Langmuir Adsorption on Fractal Surfaces - Volodymyr V. Kutarov (Adsorption Science & Technology, 2015)
We developed two new methods for analyzing the fractal characteristics of adsorbents. In the first method, the fractal dimension of the adsorbent is determined based on the Hurst index (H) calculated for the random process of development of the Langmuir isotherm. In the second method, the Langmuir isotherm is calculated from measurements of the random field of the adsorbed molecules. Then the fractal dimension is determined. using the proposed methods, we calculated the fractal dimensions of samples of xerogel at low-temperature nitrogen adsorption, lunar regolith sample at a low temperature of krypton and n-heptanes, and water vapour adsorption at ambient temperature.